3D printing and surface imprinting technologies for water treatment: A review. (October 2019) - Balogun, Hammed Abiodun; Sulaiman, Reyihangu; Marzouk, Sarah Sayed; Giwa, Adewale; Hasan, Shadi Wajih
Abstract: In recent times, 3D printing as a technology has drawn tremendous attention. Also, surface imprinting techniques in general are still evolving especially in the area of membrane design and fabrication. This paper focuses on the different 3D printing techniques in relation to the recent advances and its applications for the fabrication of module spacers and membranes for water treatment. The recent developments in surface imprinting in the area of water treatment and membrane design are also discussed in this paper. Looking at the recent developments in 3D printing technology for water treatment, revolutionary fabrication of novel membrane module components is likely to happen soon. Enhancement of 3D printing technologies in areas of materials, resolution, and speed is expected to increase the applicability of 3D printing technologies in the production of different membrane module components with high efficiency. In the near future, surface imprinting patterns of complex topography can improve performance of 3D printed membranes with applications in water purification and membrane separation.